Virtual Veneration: A Critical Inquiry into the Sacralization and Valorization of Digital Heritage in the Metaverse - Ifah Shandy; Kevin Setiawan; Khalil Jibran; Caelin Damayanti (Enigma Institute, 2025)
The emergence of the metaverse presents a paradigm shift for how cultural heritage is experienced and valued. While technical digitization is well-studied, the socio-cultural processes by which digital objects acquire profound, quasi-sacred meaning remain critically underexplored. This study undertakes a critical inquiry into